Multifunctional magnesium oxysulfate cement floor with excellent water resistance and cracking resistance
By introducing aluminum malate complex and PVB into magnesium oxysulfate cement board to form a composite structure, and combining it with an epoxy resin coating, the water resistance and crack resistance problems of magnesium oxysulfate cement are solved, realizing a high-performance, multifunctional magnesium oxysulfate cement floor.
Patent Information
- Application Number
- CN202511510245.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-22
- Publication Date
- 2026-01-13
AI Technical Summary
Existing magnesium oxysulfate cement has poor water resistance and crack resistance, and is prone to strength reduction and microcracks, especially in humid environments.
Aluminum malate complex synthesized using a specific molar ratio is combined with PVB to form a rigid-flexible composite structure. An epoxy resin-based waterborne coating is then applied to a cement substrate, and additives such as nano-silica and micron-sized alumina are added to optimize the crystal structure and pore filling.
It significantly improves the water resistance and crack resistance of magnesium oxysulfate cement board, while also giving the board high wear resistance, anti-slip and antistatic properties, making it suitable for industrial production.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of building materials, in particular to a multifunctional magnesium oxysulfate cement floor with excellent water resistance and anti-cracking performance. BACKGROUND
[0002] Magnesium oxysulfate cement is a kind of air-hardening cementitious material with light-burned magnesium oxide and magnesium sulfate as main raw materials. Compared with ordinary Portland cement, it has the advantages of light weight, fire resistance, low alkalinity, and difficulty in cracking, and has certain application prospect in the fields of building partition board and fireproof board. However, there are two fatal defects in the popularization and application of magnesium oxysulfate cement: first, its water resistance is poor, and the strength of the product will decrease significantly after long-term use in a humid environment, and it is easy to appear "returning halogen" phenomenon, that is, condensation water droplets appear on the surface due to the absorption of water in the air, which seriously affects the use experience and decoration effect; second, although its brittleness is lower than that of ordinary cement, it is still easy to produce micro-cracks under dry shrinkage or external force, which affects the integrity and long-term durability of the structure.
[0003] In order to improve the water resistance of magnesium oxysulfate cement, the existing technology usually adopts the method of adding additives for modification. Common methods include adding phosphoric acid, organic acid (such as citric acid, tartaric acid) or inorganic filler (such as fly ash, silica ash) and the like. These methods can improve the internal crystal structure or fill part of the pores to some extent, but the effect is often not significant and stable. In particular, the addition of a single organic acid mainly plays a role in retarding and controlling the crystal morphology, and has limited ability to fundamentally seal harmful capillary pores and improve long-term water resistance. At the same time, alum (potassium aluminum sulfate) as a common additive has also been tried to be used in cement system, but its direct addition usually reacts rapidly with the alkali in the system to generate coarse aluminum hydroxide precipitate, which is unevenly distributed and difficult to achieve ideal nano-level filling effect, resulting in low modification efficiency.
[0004] In terms of anti-cracking, fibers (such as glass fiber, polypropylene fiber) are usually added to improve toughness. However, the addition of fibers may have a negative impact on the fluidity of the slurry and the surface flatness, and mainly improves the macroscopic anti-cracking property, but has limited effect on inhibiting the generation of microscopic shrinkage cracks. SUMMARY
[0005] The existing technology has the problem that the conventional magnesium oxysulfate cement board has poor water resistance and anti-cracking performance. In view of the above technical problems, the present application provides a multifunctional magnesium oxysulfate cement floor with excellent water resistance and anti-cracking performance, which is composed of a base cement board and a functional coating coated on the surface of the base cement board, The base cement board comprises the following raw material components in parts by weight: Light-burned powder 50-60 parts; Magnesium sulfate aqueous solution 20-30 parts; Aluminum complex solution of organic acid 5-10 parts; PVB 0.3-2 parts; Inorganic reinforcing filler 5-10 parts; The functional coating is a coating formed by uniformly applying a functional coating on the surface of the base cement board and then curing, the functional coating is an epoxy resin-based cured water-based coating, and wear-resistant additives, anti-skid agents, and antistatic agents are simultaneously added in the coating formula, the molecular weight of the PVB ranges from 15000 to 30000 g / mol, and the Baume degree of the magnesium sulfate aqueous solution ranges from 25 to 30 °Bé.
[0006] Preferably, the aluminum complex solution of organic acid is a complex aqueous solution formed by malic acid and alum in an aqueous solution.
[0007] The preparation method of the aluminum complex solution of organic acid is as follows: (1) Dissolve malic acid in deionized water to obtain a malic acid aqueous solution with a concentration of 0.5-1 mol / L; (2) Dissolve alum in deionized water to obtain an alum aqueous solution with a concentration of 0.5-1 mol / L; (3) Take an appropriate amount of the alum aqueous solution, and add the malic acid aqueous solution dropwise while stirring to make the molar ratio of malic acid to alum in the reaction system be 2:1, stop adding the malic acid aqueous solution, and the reaction is completed to obtain the aluminum complex solution of organic acid.
[0008] Preferably, the alum is potassium alum.
[0009] Preferably, the light-burned powder is light-burned magnesium oxide prepared by calcining magnesite, the purity of the light-burned magnesium oxide is ≥80%, and the content of active magnesium oxide is ≥55%.
[0010] Preferably, the inorganic reinforcing filler includes one or more of fly ash, wollastonite powder, glass fiber, perlite powder, calcium carbonate, and slag powder.
[0011] Preferably, the epoxy resin-based cured water-based coating includes the following raw material components in parts by weight: Water-based bisphenol A type epoxy resin 60-70 parts; Water-based polyamide curing agent 15-20 parts; Wear-resistant additive 5-8 parts; Anti-skid agent 3-5 parts; Antistatic agent 2-4 parts; Film-forming aid 1-2; Defoaming agent 0.5-1 part; Thickening agent 0.3-0.8 parts; The epoxy resin-based curing waterborne coating also includes deionized water, the addition of which adjusts the solid content of the epoxy resin-based curing coating to 45-50%.
[0012] Preferably, the solid content of the waterborne bisphenol A epoxy resin is 50-55%.
[0013] Preferably, the amine value of the waterborne polyamide curing agent is 200-300 mgKOH / g.
[0014] Preferably, the wear-resistant additive is nano-silica, with an average particle size range of 20-50 nm.
[0015] Preferably, the anti-slip agent is micron-sized alumina. The preferred average particle size range is 50-100 μm.
[0016] Preferably, the antistatic agent is a quaternary ammonium salt cationic surfactant.
[0017] Preferably, the film-forming aid is propylene glycol butyl ether.
[0018] Preferably, the defoamer is an organosilicon defoamer.
[0019] Preferably, the thickener is a cellulose ether. Based on the Brookfield viscosity of a 2% aqueous solution, the viscosity of the cellulose ether measured at 20°C and 20 rpm is between 25,000 and 31,000 cps. The cellulose ether includes one or more of methylcellulose (MC), hydroxyethylcellulose (HEC), hydroxypropyl methylcellulose (HPMC), hydroxypropyl ethylcellulose (HPEC), hydroxyethyl methylcellulose (HEMC), and hydroxyethylcellulose (MEHEC).
[0020] The present invention has the following beneficial effects: (1) This invention achieves a synergistic effect of modification mechanism by introducing a pre-synthesized aluminum malate complex with a specific molar ratio into the base cement board formulation of magnesium oxysulfate cement board. This complex can slowly hydrolyze during cement hydration and curing, generating small-particle-size Al(OH)3 colloids in situ, achieving efficient and precise filling of capillary pores and gel pores within the matrix, greatly reducing porosity and optimizing pore size distribution. Simultaneously, malic acid, as a crystal regulator, is more conducive to the full growth and interweaving of the 5·1·7 phase needle-like crystals with superior water resistance. This dual effect of "crystal structure optimization" and "nanocolloid filling" essentially constructs a highly dense microstructure, qualitatively improving the water resistance and impermeability of the base cement board, and effectively inhibiting the generation of drying shrinkage microcracks; (2) This invention innovatively introduces PVB (polyvinyl butyral) as an organic toughening agent into the base cement board. PVB can form a flexible polymer network in the cement matrix, which combines with the rigid skeleton formed by the modification of aluminum malate complex to form a composite structure that combines rigidity and flexibility. This not only further improves the crack resistance and toughness of the material, enabling it to better withstand deformation and stress without easily breaking brittlely, but also the film-forming properties of PVB contribute additionally to the water resistance; (3) The present invention incorporates a specially formulated epoxy resin-based water-based coating on a base cement board. This coating not only has excellent adhesion to the modified magnesium oxysulfate substrate, avoiding problems such as peeling and flaking, but also, through the compounding of nano silica (wear-resistant), micron alumina (anti-slip), and quaternary ammonium salt antistatic agent, endows the board surface with multiple practical functions such as high wear resistance, high anti-slip properties, and permanent antistatic properties in one go. (4) The main modifiers (malic acid, alum, PVB) and water-based epoxy resin coating used in this invention are all environmentally friendly and have no strong irritating odor. The entire production process, including the pre-preparation of the complex and the molding and curing of the board, is clear, easy to operate, and does not require special or expensive equipment. It is very suitable for large-scale industrial production and has extremely high market promotion value. Detailed Implementation
[0021] The present invention will be described in detail below with reference to embodiments. However, it should be understood that the following embodiments are merely illustrative examples of implementation of the present invention and are not intended to limit the scope of the present invention.
[0022] The organic acid aluminum complex solution used in the following embodiments of the present invention is an aqueous solution of a complex formed by malic acid and alum in an aqueous solution. The preparation method of the organic acid aluminum complex solution is as follows: (1) Dissolve malic acid in deionized water to obtain an aqueous solution of malic acid with a concentration of 0.5 mol / L; (2) Dissolve alum in deionized water to obtain an alum aqueous solution with a concentration of 0.5 mol / L; (3) Take an appropriate amount of alum aqueous solution and add malic acid aqueous solution dropwise to the alum aqueous solution while stirring, so that the molar ratio of malic acid to alum in the reaction system is 2:1. Stop adding malic acid aqueous solution and the reaction ends, and an organic acid aluminum complex solution is obtained.
[0023] The waterborne bisphenol A epoxy resin used in the following embodiments of the present invention was purchased from Tianjin Intergrey Technology Co., Ltd., and its brand name is YTGR1310.
[0024] The polyvinyl butyral (PVB) used in the following embodiments of the present invention has a molecular weight of 15000 g / mol and is a thermoplastic resin formed by the condensation of polyvinyl alcohol (PVA) and butyral under acid catalysis.
[0025] The alum used in the following embodiments of the present invention is potassium alum.
[0026] The waterborne bisphenol A epoxy resin used in the following embodiments of the present invention is YTGR1310, which was purchased from Tianjin Intergrey Technology Co., Ltd.
[0027] The waterborne polyamide curing agent used in the following embodiments of the present invention was purchased from Guangdong Shuntian New Materials Co., Ltd., and its brand name is 9596W.
[0028] The preparation methods of the base cement board in the following embodiments of the present invention are all carried out according to the following methods: (1) Mix all raw materials evenly according to the formula, then inject them into the molding mold and vibrate to form the base cement board model; (2) The obtained base cement board model is dried and cured at room temperature for 24 hours. The board is taken out, cut into the required size, and sanded to make the surface of the board smooth, thus obtaining the base cement board.
[0029] The preparation methods of the multifunctional magnesium oxysulfate cement flooring with excellent water resistance and crack resistance in the following embodiments of the present invention are all carried out according to the following methods: An epoxy resin-based curing water-based coating is uniformly sprayed onto the surface of the base cement board to form an epoxy resin-based curing water-based coating. After the coating is cured at room temperature for 24 hours, a multifunctional magnesium oxysulfate cement floor is obtained.
[0030] The magnesium sulfate aqueous solution used in the following embodiments of the present invention is a solution obtained by dissolving magnesium sulfate heptahydrate in water.
[0031] Example 1
[0032] A multifunctional magnesium oxysulfate cement floor with excellent water resistance and crack resistance is composed of a base cement board and a functional coating applied to the surface of the base cement board. The base cement board has a thickness of 32mm and a size of 650mm×650mm, and the functional coating has a thickness of 0.3mm.
[0033] The base cement board is composed of the following raw material components in parts by weight: Lightly calcined magnesium oxide powder (95% purity, 65% activity) 50 parts; 20 parts of magnesium sulfate aqueous solution (25°Bé); Five parts of an organic acid aluminum complex solution; 0.3 portions of PVB; 5 parts of fly ash (30μm); The functional coating is formed by uniformly applying a functional coating to the surface of a cementitious substrate and then curing it. The functional coating is an epoxy resin-based water-based coating, and the epoxy resin-based water-based coating is composed of the following raw material components by weight: 60 parts of waterborne bisphenol A type epoxy resin; 15 parts of water-based polyamide curing agent; Wear-resistant additive (nano silica, 20nm) 5 parts; Anti-slip agent (micron-sized alumina, 50μm) 3 parts; Two parts of octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate; Propylene glycol butyl ether 1; Dow Corning DC-65 0.5 copies; Thickener (HEC, 25000 cps) 0.3 parts; The epoxy resin-based curing waterborne coating also includes deionized water, the addition of which adjusts the solid content of the epoxy resin-based curing coating to 45%.
[0034] Example 2
[0035] A multifunctional magnesium oxysulfate cement floor with excellent water resistance and crack resistance is composed of a base cement board and a functional coating applied to the surface of the base cement board. The base cement board has a thickness of 32mm and a size of 650mm×650mm, and the functional coating has a thickness of 0.3mm.
[0036] The base cement board is composed of the following raw material components in parts by weight: Lightly calcined magnesium oxide powder (90% purity, 63% activity) 54 parts; 26 parts of magnesium sulfate aqueous solution (30°Bé); 7 parts of an organic acid aluminum complex solution; 1 copy of PVB; 8 parts of wollastonite powder (50μm); The functional coating is formed by uniformly applying a functional coating to the surface of a cementitious substrate and then curing it. The functional coating is an epoxy resin-based water-based coating, and the epoxy resin-based water-based coating is composed of the following raw material components by weight: 65 parts of waterborne bisphenol A type epoxy resin; 16 parts of water-based polyamide curing agent; Wear-resistant additive (nano silica, 30nm) 6.5 parts; Anti-slip agent (micron-sized alumina, 80μm) 4 parts; 3 parts of octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate; Propylene glycol butyl ether 1.5; Defoamer (BYK-024) 0.7 parts; Thickener (MEHEC, 30000cps) 0.5 parts; The epoxy resin-based curing waterborne coating also includes deionized water, the addition of which adjusts the solid content of the epoxy resin-based curing coating to 48%.
[0037] Example 3
[0038] A multifunctional magnesium oxysulfate cement floor with excellent water resistance and crack resistance is composed of a base cement board and a functional coating applied to the surface of the base cement board. The base cement board has a thickness of 32mm and a size of 650mm×650mm, and the functional coating has a thickness of 0.3mm.
[0039] The base cement board is composed of the following raw material components in parts by weight: Lightly calcined magnesium oxide powder (85% purity, 62% activity) 60 parts; 30 parts of magnesium sulfate aqueous solution (28°Bé); 10 parts of an organic acid aluminum complex solution; Two PVB packets; 10 parts of glass fiber (50μm); The functional coating is formed by uniformly applying a functional coating to the surface of a cementitious substrate and then curing it. The functional coating is an epoxy resin-based water-based coating, and the epoxy resin-based water-based coating is composed of the following raw material components by weight: 70 parts of waterborne bisphenol A type epoxy resin; 20 parts of water-based polyamide curing agent; Wear-resistant additive (nano silica, 50nm) 6.8 parts; Anti-slip agent (micron-sized alumina, 100μm) 4.2 parts; 3.6 parts of octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate; Propylene glycol butyl ether 2; Defoamer (Dow Corning DC-65) 1 part; Thickener (HEC, 26000 cps) 0.8 parts; The epoxy resin-based curing waterborne coating also includes deionized water, the addition of which adjusts the solid content of the epoxy resin-based curing coating to 50%.
[0040] Example 4
[0041] A multifunctional magnesium oxysulfate cement floor with excellent water resistance and crack resistance is composed of a base cement board and a functional coating applied to the surface of the base cement board. The base cement board has a thickness of 32mm and a size of 650mm×650mm, and the functional coating has a thickness of 0.3mm.
[0042] The base cement board is composed of the following raw material components in parts by weight: Lightly calcined magnesium oxide powder (95% purity, 65% activity) 53 parts; 22 parts of magnesium sulfate aqueous solution (30°Bé); 5.5 parts of an organic acid aluminum complex solution; 0.8 copies of PVB; Perlite powder (70 mesh) 6.5 parts; The functional coating is formed by uniformly applying a functional coating to the surface of a cementitious substrate and then curing it. The functional coating is an epoxy resin-based water-based coating, and the epoxy resin-based water-based coating is composed of the following raw material components by weight: 63 parts of waterborne bisphenol A type epoxy resin; 18 parts of water-based polyamide curing agent; Wear-resistant additive (nano silica, 40nm) 6.5 parts; Anti-slip agent (micron-sized alumina, 60μm) 3.5 parts; 2.5 parts of octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate; Propylene glycol butyl ether 1.2; Defoamer (Dow Corning DC-65) 0.6 parts; Thickener (HEC, 25000 cps) 0.5 parts; The epoxy resin-based curing waterborne coating also includes deionized water, the addition of which adjusts the solid content of the epoxy resin-based curing coating to 46%.
[0043] Example 5
[0044] A multifunctional magnesium oxysulfate cement floor with excellent water resistance and crack resistance is composed of a base cement board and a functional coating applied to the surface of the base cement board. The base cement board has a thickness of 32mm and a size of 650mm×650mm, and the functional coating has a thickness of 0.3mm.
[0045] The base cement board is composed of the following raw material components in parts by weight: Lightly calcined magnesium oxide powder (90% purity, 63% activity) 58 parts; 27 parts of magnesium sulfate aqueous solution (30°Bé); Nine parts of an organic acid aluminum complex solution; 1.5 servings of PVB; 8 parts of slag powder; The functional coating is formed by uniformly applying a functional coating to the surface of a cementitious substrate and then curing it. The functional coating is an epoxy resin-based water-based coating, and the epoxy resin-based water-based coating is composed of the following raw material components by weight: 67 parts of waterborne bisphenol A type epoxy resin; 16 parts of water-based polyamide curing agent; Wear-resistant additive (nano silica, 45nm) 6 parts; Anti-slip agent (micron-sized alumina, 90μm) 4.5 parts; 3.6 parts of octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate; Propylene glycol butyl ether 1.8; Defoamer (Dow Corning DC-65) 1 part; Thickener (HEC, 25000 cps) 0.8 parts; The epoxy resin-based curing waterborne coating also includes deionized water, the addition of which adjusts the solid content of the epoxy resin-based curing coating to 50%.
[0046] Example 6
[0047] A multifunctional magnesium oxysulfate cement floor with excellent water resistance and crack resistance is composed of a base cement board and a functional coating applied to the surface of the base cement board. The base cement board has a thickness of 32mm and a size of 650mm×650mm, and the functional coating has a thickness of 0.3mm.
[0048] The base cement board is composed of the following raw material components in parts by weight: Lightly calcined magnesium oxide powder (95% purity, 65% activity) 56 parts; 23 parts of magnesium sulfate aqueous solution (25°Bé); 6 parts of an organic acid aluminum complex solution; 1 copy of PVB; 7 parts calcium carbonate; The functional coating is formed by uniformly applying a functional coating to the surface of a cementitious substrate and then curing it. The functional coating is an epoxy resin-based water-based coating, and the epoxy resin-based water-based coating is composed of the following raw material components by weight: 63 parts of waterborne bisphenol A type epoxy resin; 16 parts of water-based polyamide curing agent; Wear-resistant additive (nano silica, 25nm) 5 parts; Anti-slip agent (micron-sized alumina, 50μm) 3 parts; 2.3 parts of octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate; Propylene glycol butyl ether 1; Defoamer (Dow Corning DC-65) 0.5 parts; Thickener (HEC, 25000 cps) 0.3 parts; The epoxy resin-based curing waterborne coating also includes deionized water, the addition of which adjusts the solid content of the epoxy resin-based curing coating to 46%.
[0049] Comparative Example 1 is the same as Example 1, except that no organic acid aluminum complex solution was added to the base cement board in Comparative Example 1.
[0050] Comparative Example 2 is the same as Example 1, except that the base cement board in Comparative Example 2 uses a 0.5 mol / L malic acid aqueous solution and a 0.5 mol / L alum aqueous solution instead of the organic acid aluminum complex solution in Example 1. The 0.5 mol / L malic acid aqueous solution and the 0.5 mol / L alum aqueous solution are added separately to the base cement board material system. The weight parts of the 0.5 mol / L malic acid aqueous solution and the 0.5 mol / L alum aqueous solution added are 3.3 parts and 1.7 parts, respectively. The molar ratio of malic acid to alum in the added 0.5 mol / L malic acid aqueous solution and the 0.5 mol / L alum aqueous solution is approximately 2:1.
[0051] Comparative Example 3 is the same as Example 1, except that PVB was not added to the base cement board in Comparative Example 3.
[0052] Comparative Example 4 is the same as Example 1, except that the base cement board in Comparative Example 4 contains an excess of PVB, and the weight of PVB added is 5 parts.
[0053] Comparative Example 5 is the same as Example 1, except that the preparation method of the organic acid aluminum complex solution in Comparative Example 5 is as follows: (1) Dissolve malic acid in deionized water to obtain an aqueous solution of malic acid with a concentration of 0.5 mol / L; (2) Dissolve alum in deionized water to obtain an alum aqueous solution with a concentration of 0.5 mol / L; (3) Take an appropriate amount of alum aqueous solution and add malic acid aqueous solution dropwise to the alum aqueous solution while stirring, so that the molar ratio of malic acid to alum in the reaction system is 1:1. Stop adding malic acid aqueous solution and the reaction ends, and an organic acid aluminum complex solution is obtained.
[0054] Comparative Example 6 is the same as Example 1, except that the preparation method of the organic acid aluminum complex solution in Comparative Example 6 is as follows: (1) Dissolve malic acid in deionized water to obtain an aqueous solution of malic acid with a concentration of 0.5 mol / L; (2) Dissolve alum in deionized water to obtain an alum aqueous solution with a concentration of 0.5 mol / L; (3) Take an appropriate amount of alum aqueous solution and add malic acid aqueous solution dropwise to the alum aqueous solution while stirring, so that the molar ratio of malic acid to alum in the reaction system is 3:1. Stop adding malic acid aqueous solution and the reaction ends, and an organic acid aluminum complex solution is obtained.
[0055] Comparative Example 7 is the same as Example 1, except that the preparation method of the organic acid aluminum complex solution in Comparative Example 7 is as follows: (1) Dissolve citric acid in deionized water to obtain a citric acid aqueous solution with a concentration of 0.5 mol / L; (2) Dissolve alum in deionized water to obtain an alum aqueous solution with a concentration of 0.5 mol / L; (3) Take an appropriate amount of alum aqueous solution and add citric acid aqueous solution dropwise to the alum aqueous solution while stirring, so that the molar ratio of citric acid to alum in the reaction system is 2:1. Stop adding citric acid aqueous solution and the reaction ends, and an organic acid aluminum complex solution is obtained.
[0056] Comparative Example 8 is the same as Example 1, except that the preparation method of the organic acid aluminum complex solution in Comparative Example 8 is as follows: (1) Dissolve tartaric acid in deionized water to obtain an aqueous solution of tartaric acid with a concentration of 0.5 mol / L; (2) Dissolve alum in deionized water to obtain an alum aqueous solution with a concentration of 0.5 mol / L; (3) Take an appropriate amount of alum aqueous solution and add tartaric acid aqueous solution dropwise to the alum aqueous solution while stirring, so that the molar ratio of tartaric acid to alum in the reaction system is 2:1. Stop adding tartaric acid aqueous solution and the reaction ends, and an organic acid aluminum complex solution is obtained.
[0057] Comparative Example 9 is the same as Example 1, except that the preparation method of the organic acid aluminum complex solution in Comparative Example 9 is as follows: (1) Dissolve oxalic acid in deionized water to obtain an oxalic acid aqueous solution with a concentration of 0.5 mol / L; (2) Dissolve alum in deionized water to obtain an alum aqueous solution with a concentration of 0.5 mol / L; (3) Take an appropriate amount of alum aqueous solution and add oxalic acid aqueous solution dropwise to the alum aqueous solution while stirring, so that the molar ratio of oxalic acid to alum in the reaction system is 2:1. Stop adding oxalic acid aqueous solution and the reaction ends, and an organic acid aluminum complex solution is obtained.
[0058] Comparative Example 10 is the same as Example 1, except that the alum in the 0.5 mol / L alum aqueous solution used in Comparative Example 10 is ammonium alum.
[0059] Comparative Example 11 is the same as Example 1, except that Comparative Example 11 uses an equal weight portion of 0.5 mol / L malic acid aqueous solution to replace the organic acid aluminum complex solution in Example 1.
[0060] Performance testing
[0061] The multifunctional magnesium oxysulfate cement floors obtained in Examples 1-6 and Comparative Examples 1-11 of this invention were subjected to relevant performance tests. The specific test results are shown in Tables 1 and 2.
[0062] Abrasion resistance: The test standard is GB / T 1768-2006. The stronger the coating's ability to resist abrasion, the lower the abrasion loss.
[0063] Anti-slip performance: The test standard is GB / T 4100-2015. The higher the coefficient of friction, the better the anti-slip performance.
[0064] Antistatic properties: The test standard is GB / T 1410-2006. The lower the surface resistivity, the better the conductivity.
[0065] Water resistance: The product's ability to resist water damage, quantified by the softening coefficient. It is the ratio of the material's compressive strength in a saturated state to its compressive strength in a dry state. The higher the strength retention rate (softening coefficient) after immersion in water, the better the water resistance. Take the same board and cut it into two samples of the same size. The first sample (before testing, the functional coating side is facing up, and the sides and bottom are sealed with a waterproof sealant, which is a mixture of paraffin and rosin in a 1:1 mass ratio) is immersed in water for 12 hours, then removed and its compressive strength in a saturated state is tested. The second sample serves as a control, and its compressive strength in a dry state is tested. K = fsaturated / fdry, K: softening coefficient, fsaturated: compressive strength of the first sample in a saturated state, fdry: compressive strength of the second sample in a dry state. Compressive strength: The test standard is GB / T 17671-2021 ("Test Method for Strength of Cement Mortar (ISO Method)").
[0066] Crack resistance: The test standard refers to the early crack resistance test method in GB / T 50082-2024, with crack width as the evaluation index. The smaller the crack width, the better the performance.
[0067] Table 1
[0068] Table 2
[0069] Based on the above test data, we can conclude that: Comparative Example 1 showed a decrease in wear resistance, slip resistance, water resistance, crack resistance, and flexural strength due to the absence of an organic aluminum acid complex solution. The reason is that the organic aluminum acid complex in magnesium oxysulfate cement not only acts as a crystal modifier, promoting the growth of 5·1·7 phase needle-like crystals, but also slowly releases Al(OH)3 colloids during cement hydration, filling pores. Without this complex, the cement matrix lacks an effective crystal regulation and pore-filling mechanism, resulting in a loose structure and a significant decrease in water resistance and crack resistance.
[0070] In Comparative Example 2, the direct addition of malic acid and alum aqueous solution failed to effectively form a complex, thus failing to leverage the modifying effect of the complex during cement hydration and lacking effective crystal structure optimization and pore filling. The reason is that malic acid, as an organic acid, reacts rapidly with magnesium oxide when directly added to a cement system containing magnesium oxide. This reaction produces magnesium malate and water, consuming a large amount of malic acid and preventing it from effectively complexing with alum. Alum (potassium aluminum sulfate) dissolves rapidly in the cement system, releasing aluminum and sulfate ions. These ions react with hydroxide and calcium ions produced during cement hydration, forming precipitates such as aluminum hydroxide. Due to the rapid dissolution and reaction of alum, the released aluminum ions do not have sufficient opportunity to form a complex with malic acid. Instead, aluminum ions tend to combine with other ions in the cement hydration products, forming precipitates without a slow-release effect. Therefore, when malic acid and alum are added individually, they react rapidly with other components in the cement system, preventing the formation of a large amount of organic acid-aluminum complex. Even if a small amount of organic aluminum acid complexes are formed, because they are randomly generated during cement hydration, they cannot have the controlled, slow-release effect of pre-synthesized organic aluminum acid complexes. This results in the release of aluminum ions not being synchronized with the cement hydration reaction, thus failing to effectively utilize the complexes in optimizing crystal structure and filling pores. Consequently, the material's water resistance, crack resistance, and other properties are significantly reduced. Therefore, pre-synthesizing organic aluminum acid complexes and adding them as additives to cement material systems is a key step in improving the performance of magnesium oxysulfate cement boards.
[0071] Comparative Example 3, without the addition of PVB, lacked the toughening effect of the resin network, resulting in a significant decrease in crack resistance and flexural strength. The reason is that PVB, as an organic toughening agent, forms a flexible polymer network in the cement matrix, combining with the rigid skeleton to improve the material's crack resistance and toughness. Without PVB, the material's toughness is reduced, making it prone to brittle fracture.
[0072] In Comparative Example 4, excessive PVB addition resulted in excessively high system viscosity, affecting its uniform dispersion in the cement matrix and thus preventing the formation of an effective polymer network.
[0073] In Comparative Examples 5 and 6, the improper molar ratio of malic acid to alum in the organic acid-aluminum complexes weakened the complexation effect, hindering effective crystal structure optimization and pore filling. The molar ratio of malic acid to alum is crucial for the formation and stability of the complexes. An improper molar ratio leads to unstable complex structures, preventing the effective release of Al(OH)3 colloids and the regulation of crystal growth. For example, excessive malic acid may increase the amount of free malic acid in the solution, affecting the hydration reaction and crystal structure of cement; excessive alum may cause uncomplexed aluminum ions to affect the setting time and strength development of cement.
[0074] Comparative Examples 7, 8, and 9, using other organic acids (citric acid, tartaric acid, and oxalic acid) to complex with alum, showed limited improvement in performance and even had negative effects. The slow-release effect of the complexes formed by citric acid and tartaric acid with alum during cement curing was inferior to that of the aluminum malate complex. This may be because the molecular structure or complexing ability of citric acid and tartaric acid causes them to release aluminum ions too quickly or too slowly in the cement hydration environment, failing to synchronize with the cement hydration reaction, thus affecting the formation of Al(OH)3 colloids and the optimization of crystal structure. Due to poor slow-release effect and insufficient crystal growth control, the citric acid and aluminum tartaric acid complexes could not effectively fill the pores in the cement matrix, resulting in high porosity and decreased material properties. The complexes formed by oxalic acid and alum had poor stability and easily decomposed during cement hydration, releasing free oxalic acid and aluminum ions. Free oxalic acid may affect the cement hydration reaction, leading to abnormal setting time or poor strength development. Example 1, by optimizing the molar ratio of malic acid to alum, forms a stable aluminum malate complex, achieving the slow release of aluminum ions and the effective generation of Al(OH)3 colloids during cement hydration. Simultaneously, it regulates the growth of 5·1·7 phase needle-like crystals, forming a dense crystal network. Furthermore, the addition of PVB further enhances the material's toughness and crack resistance. In contrast, Comparative Examples 1-8, due to the absence of key components, improper addition methods, unreasonable component ratios, or the use of ineffective organic acids, failed to achieve effective modification, resulting in a significant decline in material performance. Therefore, the formulation and process conditions of Example 1 have significant advantages in improving the performance of magnesium oxysulfate cement boards.
[0075] The use of ammonium alum in Comparative Example 10 may affect the pH value and stability of the system, potentially leading to unstable water resistance. During cement hydration, changes in pH value may affect crystal growth and interlocking, thereby affecting the material's water resistance and impermeability.
[0076] In Comparative Example 11, only malic acid was added, but it did not form a complex with alum, thus failing to exert the modifying effect of the complex during cement hydration. When malic acid exists alone, its modifying effect on the cement matrix is limited.
[0077] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.
Claims
1. A multifunctional magnesium oxysulfate cement floor with excellent water resistance and crack resistance, characterized in that, It is composed of a base cement board and a functional coating applied to the surface of the base cement board. The base cement board comprises, by weight, the following raw materials: 50-60 parts of lightly charred powder; 20-30 parts magnesium sulfate aqueous solution; 5-10 parts of an organic acid aluminum complex solution; PVB 0.3-2 portions; 5-10 parts of inorganic reinforcing filler; The functional coating is formed by uniformly applying a functional coating to the surface of a base cement board and then curing it. The functional coating is an epoxy resin-based water-based coating, and the coating formulation contains wear-resistant additives, anti-slip agents, and antistatic agents. The molecular weight of the PVB ranges from 15,000 to 30,000 g / mol.
2. The multifunctional magnesium oxysulfate cement flooring with excellent water resistance and crack resistance according to claim 1, characterized in that, The organic acid aluminum complex solution is an aqueous solution of a complex formed by malic acid and alum in an aqueous solution.
3. The multifunctional magnesium oxysulfate cement flooring with excellent water resistance and crack resistance according to claim 2, characterized in that, The molar ratio of malic acid to alum is 2:
1.
4. The multifunctional magnesium oxysulfate cement flooring with excellent water resistance and crack resistance according to claim 2, characterized in that, The alum is potassium alum.
5. The multifunctional magnesium oxysulfate cement flooring with excellent water resistance and crack resistance according to claim 1, characterized in that, The light-burned powder is calcined magnesium oxide made from magnesite as raw material. The purity of the light-burned magnesium oxide is ≥80%, and the active magnesium oxide content is ≥55%.
6. The multifunctional magnesium oxysulfate cement flooring with excellent water resistance and crack resistance according to claim 1, characterized in that, The inorganic reinforcing filler includes one or more of the following: fly ash, wollastonite powder, glass fiber, perlite powder, calcium carbonate, and slag powder.
7. The multifunctional magnesium oxysulfate cement flooring with excellent water resistance and crack resistance according to claim 1, characterized in that, The epoxy resin-based curable waterborne coating comprises, by weight, the following raw material components: 60-70 parts of waterborne bisphenol A type epoxy resin; 15-20 parts of water-based polyamide curing agent; 5-8 parts of wear-resistant additive; 3-5 parts anti-slip agent; 2-4 parts antistatic agent; Film-forming aids 1-2; 0.5-1 part defoamer; Thickener 0.3-0.8 parts; The epoxy resin-based curing waterborne coating also includes deionized water, the addition of which adjusts the solid content of the epoxy resin-based curing coating to 45-50%.
8. The multifunctional magnesium oxysulfate cement flooring with excellent water resistance and crack resistance according to claim 7, characterized in that, The wear-resistant additive is nano-silica with an average particle size of 20-50 nm.
9. The multifunctional magnesium oxysulfate cement flooring with excellent water resistance and crack resistance according to claim 7, characterized in that, The anti-slip agent is micron-sized alumina with an average particle size of 50-100 μm.
10. The multifunctional magnesium oxysulfate cement flooring with excellent water resistance and crack resistance according to claim 7, characterized in that, The antistatic agent is a quaternary ammonium salt cationic surfactant.